(untitled) (Journal of Forensic Medicine & Toxicology, 2011)
In this editorial article, general aspects of Forensic Medicine practice, working arrangement and problems in the field are covered. It also provides a reasonable solution to common problems and an answer to ambiguous working areas in day to day working. Readers are expected to give feedback on the issues of their concern. We plan to draft Manual for Working arrangement in Medico-legal practice and draft SOPs (Standard Operative Procedures) for the specialty in future.